PORTRAYING HIGH FOREIGN LANGUAGE LISTENING ANXIETY STUDENTS’ ENGAGEMENT IN THE IMPLEMENTATION OF NARROW LISTENING - Refi Ranto Rozak (PROJECT (Professional Journal of English Education), 2023)
The article aims at portraying the learning engagement of high foreign language listening anxiety students in the implementation of narrow listening. The participants of the study consist of 42 English language education students with high foreign language listening anxiety of a private teacher training and education college in Jawa Timur province. This study used a case study method to observe the phenomenon of a listening activity. The data were collected through observation technique by using field notes. The collected data were then analyzed by using coding analysis. The results show that students have positive and negative behavioral, emotional and cognitive engagement dimensions.